Association Between Thyroid Dysfunction and Pre-eclampsia with Severe Features - Dey, Laboni; Zebunnesa, Moshammat; Sen, Suman; Begum, Mortuza; Tabassum, Tamanna; Akter, Farzana; Sen, Kanon; Chowdhury, Fahmida Islam; Rashid, Fahmida; Akter, Shahena (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: The physiological changes in the thyroid gland during pregnancy are well understood but only a few reports provide information about thyroid function in complicated pregnancies, like preeclampsia with severe features, especially from Bangladesh. Hence this study was done to establish an association between thyroid dysfunction with preeclampsia with severe features in our population. Materials and methods: In this case-control study, 50 preeclamptic women with severe features (Case) and 50 normotensive pregnant women (Control) were selected from the Obstetrics & Gynecology Department of Chittagong Medical College Hospital. Thyroid profile (Free triiodothyronine [FT3], Free thyroxine [FT4] and Thyroid Stimulating Hormone [TSH]) was measured by the Chemiluminescent Immunoassay (CLIA) technique. Results: The mean serum TSH level in cases was increased significantly than in the control (3.69±1.32 mIU/L versus 2.42±0.96mIU/L,p<0.001). Serum T3 (2.51±0.26 Pg/ml versus 2.70±0.43pg/ml, p=0.006) and T4 levels (1.0±0.28 ng/dl versus 1.12±0.23ng/dl,p=0.024) were decreased significantly in preeclamptic women when compared to controls. Thirty-eight per centof the preeclamptic women had TSH titers>4mIU/ml as compared to 8% in the controls (p<0.001). The odd ratio corresponding to TSH titers> 4mIU/ml in preeclamptic women with severe features was 3.44 (95%, CI=1.38-8.53). Conclusions: These results indicate that thyroid function is altered in preeclampsia with severe features and pregnancy with hypothyroidism are more susceptible to develop Pre-eclampsia with severe features. JCMCTA 2023 ; 34 (1) : 100-105